ESR, physical and structural studies on Mn2+ doped in mixed alkali phosphate glasses. (2021) - Jerroudi, M.; Bih, L.; Haily, E.; Bejjit, L.; Haddad, M.; Manoun, B.; Lazor, P.
Abstract: Glass formation and properties of manganese phosphate glasses containing both Na2 O and K2 O oxides with the general formula 49.95[xNa2 O-(1-x)K2 O]-0.1MnO2 -49.95P2 O5 with x = 0–1 mol%, have been investigated. The vitreous samples were prepared by standard melt quenching. To get an insight into their physical properties, the density and the glass transition temperature were procedure determined. The structure of the glass was performed by Infrared, Raman, and electron spin resonance (EPR) spectroscopies. The results obtained by these techniques have allowed us to explain their structure and properties upon the variation of the chemical composition. The variation of the glass transition temperature as a function of the composition presents a minimum for the ratio Na/Na + K = 0.5. Infrared and Raman spectroscopies has identified the presence of different structural grouping units in the glassy-network. It is found that the stretching vibration νs (PO2 ) − and νs (P–O–P) are more sensitive to the substitution of alkali elements. EPR experiments have shown the presence of Mn 2+ centers in the glasses. The variation of the g-factor as a function of the composition is non-linear. The non-linearity behavior of the composition dependence of Tg, vibration bending mode, and the g-factor are a fingerprint of the mixed alkali effect in the glasses under study.